Evaluation of cefepime kinetic variables and milk production volume in goats - Lacchini, Raúl (2004)
The objective of the present work was to investigate the correlation between the kinetic variables, and the volume of milk production, with and without a local inflammatory reaction induced by subcutaneous implants of a device for collecting tissue fluid.\n\n(Párrafo extraído del texto a modo de resumen)